Selection of wheat (Triticum aestivum) variety through expert system - ISLAM, SHAHNAWAZUL; KUNDU, SUSHILA; SHORAN, JAG; SABIR, NAVED; SHARMA, KIRTI; FAROOQI, SAMIR; SINGH, RANDHIR; AGARWAL, HARI OM; CHATURVEDI, K K; SHARMA, R K; SHARMA, A K (The Indian Journal of Agricultural Sciences, 2012)
Most of the released wheat (Triticum aestivum L. emend Fiori & Paol.) varieties have been documented for various characteristics that they possess. The challenge was to organize these varieties electronically so that the farmers of the country could be benefited from this information for increase in production. Researchers and students could use them for reference and include them in their future research programmes. An expert system on wheat crop management has been developed for this purpose. The system has an exclusive variety selection module with a scientific knowledge base in the background. The module suggests a variety of farmer’s/user’s choice based on location and desired characteristics like sowing condition, yield, protein content, response to diseases and insects. The system carries detailed information about 300 varieties that have been stored in its knowledge base.